Clinical Guideline Highlights for the Hospitalist: Diagnosis and Management of Clostridium difficile in Adults. Issue 2 (18th September 2019) - Parsons, Andrew S; Burger, Alfred; Pahwa, Amit K
Abstract : GUIDELINE TITLE: 2018 Infectious Disease Society of America (IDSA)/Society for Healthcare Epidemiology of America (SHEA) Clostridium difficile infection (CDI) clinical practice guideline RELEASE DATE: February 15, 2018 PRIOR VERSION: 2010 Infectious Disease Society of America (IDSA)/Society for Healthcare Epidemiology of America (SHEA) Clostridium difficile infection (CDI) clinical practice guideline DEVELOPER: A panel of 14 multidisciplinary experts FUNDING SOURCE: IDSA and SHEA TARGET POPULATION: Adult and pediatric patients at risk for or diagnosed with Clostridium difficile infection based on a literature review with a defined search period of 2009–2016. This review will focus on adult patients.